SOSIALISASI PENANAMAN NILAI KARAKTER MANDIRI SUB NILAI KEBERANIAN UNTUK MEWUJUDKAN GENERASI ANTI KORUPSI SISWA KELAS VI DI SD GMIT KOLHUA KOTA KUPANG - Tresli Marlen Kolioe; Greandly Ferselia Liu; Mateos Nalle; Rely Putrini Taunus; Yokha Rosdiana Nullek (Pengabdian Masyarakat Ilmu Pendidikan, 2022)
Abstrak Korupsi adalah suatu tindakan kriminal. Tidak sedikit dari sekian banyak orang melakukan korupsi,yang mana fenomena inilah yang menjadi keprihatinan banyak kalangan. Tujuan diberikannya mata pelajaran Pendidikan anti korupsi ini diharapkan mampu membentuk generasi yang bebas korupsi. Metode yang digunakan adalah metode sosialisasi kepada siswa tentang pendidikan anti korupsi Aku Anak yang Jujur,Disiplin,dan Bertanggung. Pendidikan anti korupsi melalui jalur Pendidikan lebih efektif karena dapat merubahan sikap,mental yang terjadi pada diri seseorang, dan melalui jalur ini lebih bersistem serta lebih mudah diukur,yaitu perubahan perilaku anti korupsi. Oleh karena itu Penanaman sikap antikorupsi merupakan hal yang wajib dan harus ditanamkan kepada anak mulai dari usia dini pada lingkungan sekolah. Abstract Corruption is a criminal act. Not a few of the many people commit corruption, which is a phenomenon that is a concern for many people. The purpose of providing anti-corruption education subjects is expected to be able to form a corruption-free generation. The method used is the method of socialization to students about anti-corruption education I am an Honest, Disciplined, and Responsible Child. Anti-corruption education through education is more effective because it can change the mental attitude that occurs in a person to Corruption is a criminal act. Not a few of the many people commit corruption, which is a phenomenon that is a concern for many people. The purpose of providing anti-corruption education subjects is expected to be able to form a corruption-free generation. The method used is the method of socialization to students about anti-corruption education I am an Honest, Disciplined, and Responsible Child. Anti-corruption education through education is more effective because it can change the mental attitude that occurs in a person, and through this route it is more systematic and easier to measure, namely changes in anti-corruption behavior. Therefore, instilling an anti-corruption attitude is mandatory . Therefore, instilling an anti-corruption attitude is mandatory and must be instilled in children from an early age in the school environment.